2003
DOI: 10.1080/09515080307771
|View full text |Cite
|
Sign up to set email alerts
|

Intentional action in folk psychology: An experimental investigation

Abstract: Abstract:Four experiments examined people's folk-psychological concept of intentional action. The chief question was whether or not evaluative considerations -considerations of good and bad, right and wrong, praise and blame -played any role in that concept. The results indicated that the moral qualities of a behavior strongly influence people's judgements as to whether or not that behavior should be considered 'intentional.' After eliminating a number of alternative explanations, the author concludes that thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
262
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(276 citation statements)
references
References 15 publications
11
262
1
2
Order By: Relevance
“…This asymmetry in intentional action attributions has been replicated with other scenarios (Knobe, 2003b;Knobe & Mendlow, 2004;Mallon, 2008;Nadelhoffer, 2004aNadelhoffer, , 2006Shepard & Wolff, 2013;Uttich & Lombrozo, 2010;Wright & Bengson, 2009), with children as young as four years (Lesle, Knobe, & Cohen, 2006), with participants who suffer from deficits in emotional processing due to lesions in the ventromedial prefrontal cortex (Young, Cushman, Adolphs, & Hauser, 2006), and, for at least some versions of the scenarios, with adults with high functioning autism or Asperger's (Zalla & Leboyer, 2011;Zalla, Machery, & Leboyer, 2010). The asymmetry has also been reported with word changes in the original script introducing varying concepts such as intention and intending (McCann, 2005), deciding, being in favor of, advocating for (Pettit & Knobe, 2009), knowledge (Beebe & Buckwalter, 2010), belief (Beebe, 2013;Tannenbaum, Ditto, & Pizarro, 2007), awareness (Tannenbaum et al, 2007) remembering (Alfano, Beebe, & Robinson, 2012), and desire (Guglielmo & Malle, 2010;Tannenbaum et al, 2007).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…This asymmetry in intentional action attributions has been replicated with other scenarios (Knobe, 2003b;Knobe & Mendlow, 2004;Mallon, 2008;Nadelhoffer, 2004aNadelhoffer, , 2006Shepard & Wolff, 2013;Uttich & Lombrozo, 2010;Wright & Bengson, 2009), with children as young as four years (Lesle, Knobe, & Cohen, 2006), with participants who suffer from deficits in emotional processing due to lesions in the ventromedial prefrontal cortex (Young, Cushman, Adolphs, & Hauser, 2006), and, for at least some versions of the scenarios, with adults with high functioning autism or Asperger's (Zalla & Leboyer, 2011;Zalla, Machery, & Leboyer, 2010). The asymmetry has also been reported with word changes in the original script introducing varying concepts such as intention and intending (McCann, 2005), deciding, being in favor of, advocating for (Pettit & Knobe, 2009), knowledge (Beebe & Buckwalter, 2010), belief (Beebe, 2013;Tannenbaum, Ditto, & Pizarro, 2007), awareness (Tannenbaum et al, 2007) remembering (Alfano, Beebe, & Robinson, 2012), and desire (Guglielmo & Malle, 2010;Tannenbaum et al, 2007).…”
Section: Introductionmentioning
confidence: 81%
“…For example, numerous findings report that people are much more likely to judge that bad outcomes are brought about intentionally compared to good outcomes, the socalled side-effect effect or Knobe effect (original research by Knobe, 2003aKnobe, , 2003bKnobe, , 2005Knobe, , 2006Knobe, , 2010Knobe & Mendlow, 2004; see additional studies by Cova & Naar, 2012;Cushman & Mele, 2008;Ditto, Pizarro, & Tannenbaum, 2009;Lanteri, 2012;Nadelhoffer, 2004aNadelhoffer, , 2004bNadelhoffer, , 2005Nadelhoffer, , 2006Pellizzoni, Girotto, & Surian, 2010;Sousa & Holbrook, 2010;Wright & Bengson, 2009). The side-effect effect has been claimed to reflect deep and fundamental facts about human cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Prior behavioral work, for example, has shown that participants judge impulsive crimes (e.g., crimes of passion) as less morally blameworthy than deliberate or premeditated crimes but impulsive and deliberate charitable behavior as equally morally praiseworthy (D. Pizarro, et al, 2003). In other research, participants have been shown to attribute greater intent to agents bringing about negative versus positive side-effects (Knobe, 2003(Knobe, , 2005. In one example, a CEO implements a profitable program, foreseeing that he will help / harm the environment as a side-effect of his action, though he has no intention to help / harm the environment.…”
Section: An Asymmetry Between Blame and Praisementioning
confidence: 99%
“…Finally, it is worth noting a potential connection between our research and the widespread, surprising presence of moral norms in disparate corners of the human mind: e.g., in causal reasoning and mental state attribution (10,25,26,29,36). These processes also involve reasoning over a set of possibilities.…”
Section: Study 3: Default Modal Representations In High-level Cognitionmentioning
confidence: 99%